THE EFFECT OF GREEN TEA CONSUMPTION ON BLOOD PRESSURE: EVIDENCE BASED CASE REPORT - Yulia Tri Anggini Nirwani Suwandi; Nurul Ratna Mutumanikam (Perhimpunan Dokter Gizi Klinik Indonesia, 2026)
Background: Cardiovascular disease (CVD) remains the leading cause of mortality worldwide. Hypertension is one of the most prevalent forms of CVD. Although systemic therapies have substantially advanced, adjunctive interventions are still needed to improve clinical outcomes. Green tea has been extensively investigated as a potential adjunctive therapy in the management of CVD. Objective: To evaluate the effect of green tea consumption on blood pressure. Methods: A systematic literature search was conducted using the PubMed, Cochrane Library, and Google Scholar databases, focusing on publications from 2020 to 2025. Eligible studies included randomized controlled trials (RCTs), systematic reviews, and meta-analyses involving adult patients with cardiovascular disease who consumed green tea. Study quality was assessed using the criteria of the Oxford Centre for Evidence-Based Medicine (CEBM). Results: Three studies met the inclusion criteria. The systematic review and meta-analysis of RCTs by Rezaei et al and Renfan et al. reported a significant effect on the improvement of both systolic and diastolic blood pressure. In contrast, the RCT by Pathania et al. demonstrated improvement only in systolic blood pressure, with no comparable effect on diastolic pressure in the intervention group. These studies reported inconsistent findings, with much of the available evidence derived from observational data lacking clearly defined dosages. Major limitations included small sample sizes, heterogeneous populations, and inconsistent outcome reporting Conclusion: Green tea consumption may reduce both systolic and diastolic blood pressure. However, stronger evidence from large-scale clinical trials is required to confirm its efficacy and support clinical implementation.